Customer Relationship Management, Sebuah Bentuk Komunikasi Perusahaan untuk Menjaga Kelestarian Pelanggan - Oktophilus, Mikhael (Applied Business and Administration Journal, 2022)
The complexity of customer needs or desires makes companies increasingly motivated to provide the best products/services by adjusting the characteristics of the customers themselves. The pattern of service to customers has shifted, which initially considered the customer as a buyer in a transactional relationship, now it has shifted slightly to a more positive one, namely that the customer is a long-term asset for the company's sustainability. With the implementation of Customer Relationship Management, companies have full awareness to build relationships with them, in order to streamline and streamline the company's funds, energy, and time. Customer information is obtained from the data they provide to the company, ranging from general to private. The rest of the use of Customer Relationship Management still boils down to the company's ability to translate customer persona information, and make decisions on that information. Feedback given by customers on what they feel is very valuable to the company, and with an awareness of renewal, it is appropriate for the company to respond to complaints or feedback given from the customer's point of view.